EAD: entre a ferramenta e a língua perfeita: um estudo discursivo sobre aprendizagem de língua inglesa como língua estrangeira a distância - Amado, Giselly Tiago Ribeiro (2018)
This work was aimed to understand how English learning occurred in a distance learning graduation course in Letters-English at Uberlandia Federal University (UFU). For this, we analyzed responses to a questionnaire with open-ended questions applied to former students. We point out that the motivation for this research was precisely the fact that we were questioned to comprehend the representations about language, learning and technologies existing in the course. Therefore, our research questions were composed as follows: how were this distance learning course in Letters-English and the English (learning) discoursivizated by the survey respondents? Which representations of language and distance learning in the context of this research do we deal with? What do these representations tell us about the English teaching and learning larger context by distance learning in Brazil nowadays? This was the first Letters-English graduation class in distance learning at UFU, that offered the course from 2011 to 2015 within The National Plan for Elementary Education Teacher Training - PARFOR distance learning. For the development of this work we mobilized the theoretical assumptions of Michel Pêcheux, and also questions of Applied Linguistics, from post-colonial and cultural studies. Thus we follow, a discursive perspective, from which we reflect on the language in its relation with the history and the ideology and on discursive processes of sense production. We deal with some basic concepts as: discourse, subject, discursive memory and imaginary formations, in which we get the support for the corpus analysis, which was composed by the transcription of the AREDA Questionnaire, elaborated by Serrani-Infante, then, AREDA was our theoretical and methodological support for data collection. As a result it was possible to understand that the relation of the survey respondents, with regard to the discoursivization on English and distance learning course, pushes through four representations, namely as: a) Distance Learning Representation; b) Teachers Representation in the English teaching-learning process; c) English Representations; and d) English Fluency Representation. These representations intertwine and interwoven when the participants enunciate of themselves and their experiences, at which point we perceive the discursive resonances that imply distance learning as something, estrangement, at first, by the innovation modality, and then, as a tool. Distance learning, in this discoursivization, refers to the future, as well as the English is also significance for the future, but in an idealized, unattainable way, as a perfect language.